Metode Pembelajaran Tahfiz Al-Quran di PKBM Markazul Qur’an Sumatera Barat - Adam Mudinillah; Amelia Putri (Mitra PGMI: Jurnal Kependidikan MI, 2021)
PKBM Markazul Qur’an West Sumatra, which is in Padang Panjang City, is a foundation with the form of PKBM education (Center for Community Learning Activities), which has been around for almost 14 years. Besides being well-known as a foundation for memorizing the Koran, PKBM Markazul Qur’an West Sumatra is also a school that implements the 2013 curriculum. There are five methods used in memorizing the Quran in Markazul Qur'an, namely a) Talaqqi Method, b) Wahdah Method, c) Halaqah Method, d) Murajaah Method, and e) Sima’i/Tasmi’. This study used a qualitative approach to describe a situation and observed phenomenon with writing, data, and information.